Playfulness and seriousness in Plato’s dialogues - Guzmán Mesa, Eufrasio (Estudios de Filosofía, 1990)
The relationship between these two tenns is studied in several of Plato’s dialogs. It is shown that both of them suppose spiritual attitudes which, though different, are not always mutually excluding. The playful attitude was in sorne cases attached to an undesirable disposition for philosophichal enquiry; the serious attitude was recognized as being the regulator of this same activity. However, dialectic is presented in different occasions as "a difficult game". Plato evidently recognized a playful dimension of language, very visible in writing, without which it would be impossible to attempt approaching the thing; however, he simultaneously posed its limitation, by means of the serious disposition proper to philosophy.